The Effectiveness of Spirulina in Restoring Body Weight in Anemia-Induced Female Wistar Rats - Zahra Konitah; Sajidan Sajidan; Artini Pangastuti (Universitas Islam Negeri Walisongo Semarang, 2025)
One of the most prevalent health problems in Indonesia is anemia, particularly among adolescent girls, where concerns about excessive weight gain may reduce adherence to iron supplementation. Spirulina is a potential alternative supplement rich in iron and nutrients that support hematopoiesis and may address these concerns. This study aimed to analyze the effect of spirulina supplementation on body weight in anemic adolescent female Wistar rats. This experimental study used 25 female Wistar rats divided into five groups: normal control (NC) received a standard BR diet, positive control (PC) received a low-iron diet to induce anemia, and three treatment groups received spirulina at doses of 25, 50, and 100 mg/kg body weight (T1–T3) for 21 days. Body weight was measured before anemia induction, after anemia induction, and following supplementation. The results showed a significant overall difference in body weight gain among the groups (p < 0.001), which was mainly driven by differences between the normal control and positive control groups. However, post hoc analysis indicated no significant differences in body weight gain between the positive control group and treatment groups 1, 2, and 3 (p > 0.05). Body weight in the treatment groups increased by 22.8–27 g, indicating recovery toward baseline values. Although these differences were not statistically significant, spirulina supplementation may contribute to anemia recovery, as reflected by improvements in body weight. In conclusion, spirulina shows potential as a nutritional supplementation strategy that does not induce excessive weight gain while supporting iron-related nutritional needs.